Vida Saludable: Sitios web confiables - Linda B. Bobroff; Leigh Ann Martin (EDIS)
The number of resources available online grows every day. Unfortunately, there are no regulations to ensure that the information on these websites is accurate. Older adults can readily access reliable information on the Internet by focusing on government and education sites. This 3-page fact sheet is a major revision of the Spanish-language version of FCS-8587/FY102: Healthy Living: Reliable Websites. It provides a list of trustworthy Internet sources related to nutrition, health, food safety, and general interest for older adults. Written by Linda B. Bobroff and Leigh Ann Martin, and published by the UF Department of Family, Youth and Community Sciences, revised November 2015.